Analisis Highest and Best Use Pada Jalan Dr. Ir. H. Soekarno Nomor 440-484 (MERR) - Surabaya - Fahmi Firdaus Alrizal; Siti Choiriyah; Firmansyah Putra Pratama (Jurnal Teknik Sipil, 2021)
The potential development of vacant land in Surabaya continues to increase. Especially on Jalan Dr. Ir. H. Soekarno Surabaya City number 440-448. In the land area, there are 2 apartment buildings, 1 hotel building, 1 housing estate, 45 office buildings, 6 shop houses, 43 restaurant buildings, 1 clinical laboratory building, 20 house buildings, 50 shopping buildings, 1 college building, and 4 school buildings. . So from such data, Dr. Ir. H. Soekarno Surabaya City number 440-448. So the area has the potential to attract investment. The Detailed Spatial Planning (RDTR) and Zoning Regulations UP 1 Rungkut 2014 state that the direction of development along Dr. Ir. H. Soekarno (MERR) in trade and service activities, as well as housing activities (vertical housing) also has the potential to develop. In order to find out which buildings are profitable on the land area, this is done by using the Highest and Best Use analysis. The analysis can take advantage of a vacant land or increase a property that is physically feasible, legally permitted, financially feasible, and has maximum productivity that comes from the highest increase in land value if a building is erected. Based on the results of data analysis on the legal, physical, financial, and maximum productivity aspects of the vacant land. So, it can be concluded that if a shop is built, the land value is Rp. 24,726,872 and land productivity of 126%, whereas if an office is built, the land value is Rp. 23,013,522 and land productivity of 117%. So that the shopping property is the best and highest alternative use that is suitable to be developed on the vacant land.